2018
DOI: 10.1038/s41467-018-06108-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of polymorphism and selection in the subgenomes of the allopolyploid Arabidopsis kamchatica

Abstract: Genome duplication is widespread in wild and crop plants. However, little is known about genome-wide selection in polyploids due to the complexity of duplicated genomes. In polyploids, the patterns of purifying selection and adaptive substitutions may be affected by masking owing to duplicated genes or homeologs as well as effective population size. Here, we resequence 25 accessions of the allotetraploid Arabidopsis kamchatica, which is derived from the diploid species A. halleri and A. lyrata. We observe a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 68 publications
6
73
0
Order By: Relevance
“…This suggests that natural selection may be biased toward the B subgenome in wild A. monticola , but domestication has larger effects on the A subgenome of cultivated A. hypogaea . These data suggest a role for asymmetric selection in expression divergence between homoeologous genes and subgenomes of peanuts …”
Section: Resultsmentioning
confidence: 80%
“…This suggests that natural selection may be biased toward the B subgenome in wild A. monticola , but domestication has larger effects on the A subgenome of cultivated A. hypogaea . These data suggest a role for asymmetric selection in expression divergence between homoeologous genes and subgenomes of peanuts …”
Section: Resultsmentioning
confidence: 80%
“…Presently, our results provide a testable hypothesis to explain the observed correlation of polyploidy and crop domestication 10 .More broadly, our results suggest that paleopolyploidy may leave behind a legacy of elevated genetic diversity across the duplicated remnants of diploidized genomes. Although most models and studies of polyploid evolution compare diploids and polyploids11,12,14,16,17,19,[70][71][72] , our comparison of paleologs and non-paleologs within a diploidized paleopolyploid uncovered evidence for similar dynamics ongoing within plant genomes even millions of years after whole genome duplication. The extensive genome duplication history of plants may result in genomes with different levels of diversity based on the mechanisms of gene origin.…”
mentioning
confidence: 88%
“…Polyploidy often precedes domestication and crops are nearly twice as likely to be domesticated in lineages with a relatively recent WGD compared to those without 10 . Among the potential explanations for the relationship between polyploidy and domestication, the expanded genetic diversity and plasticity of polyploid plants may be especially advantageous during domestication and crop improvement [11][12][13][14][15] . Analyses in yeast have shown that polyploid lineages not only have higher genetic diversity but also adapt to new environments faster than their lower ploidal level relatives 16 .…”
Section: Introductionmentioning
confidence: 99%
“…gemmifera and A. l . petraea (Shimizu‐Inatsugi et al., ; Paape et al., ). It is likely to have spread outward from Japan to eastern Russia, across the Bering land bridge to Alaska, and down the western edge of Canada (Shimizu‐Inatsugi et al., ).…”
mentioning
confidence: 99%
“…Arabidopsis kamchatica is an allotetraploid that originated ~64,000-145,000 years ago from hybridization of diploid A. h. gemmifera and A. l. petraea (Shimizu-Inatsugi et al, 2009;Paape et al, 2018). It is likely to have spread outward from Japan to eastern Russia, across the Bering land bridge to Alaska, and down the western edge of Canada (Shimizu-Inatsugi et al, 2009).…”
mentioning
confidence: 99%